2008
DOI: 10.1152/jn.90321.2008
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor and Reflex Adaptation After Partial Denervation of Ankle Extensors in Chronic Spinal Cats

Abstract: This work investigates the capacity of the spinal cord to generate locomotion after a complete spinal section and its ability to adapt its locomotor pattern after a peripheral nerve lesion. To study this intrinsic adaptive capacity, the left lateral gastrocnemius-soleus (LGS) nerve was sectioned in three cats that expressed a stable locomotion following a complete spinal transection. The electromyograph (EMG) of multiple hindlimb muscles and reflexes, evoked by stimulating the left tibial (Tib) nerve at the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Changes within the functional connectivity of the CPG following a lesion within the intrinsic circuitry have also been reported in mollusks, explaining recovery of escape behavior without the need for regeneration (Sakurai and Katz 2009). In addition, and in accordance with our results, several studies have previously shown asymmetric changes imprinted in the spinal circuitry that were revealed by a complete SCI Rossignol 2003a, 2003b;Frigon and Rossignol 2008;). …”
Section: Discussionsupporting
confidence: 93%
“…Changes within the functional connectivity of the CPG following a lesion within the intrinsic circuitry have also been reported in mollusks, explaining recovery of escape behavior without the need for regeneration (Sakurai and Katz 2009). In addition, and in accordance with our results, several studies have previously shown asymmetric changes imprinted in the spinal circuitry that were revealed by a complete SCI Rossignol 2003a, 2003b;Frigon and Rossignol 2008;). …”
Section: Discussionsupporting
confidence: 93%
“…This idea is supported by reported changes in gains of proprioceptive feedback [Pearson and Misiaszek, 2000;Frigon and Rossignol, 2008;Donelan et al, 2009] and central drive to intact synergists [Gritsenko et al, 2001;Maas et al, 2010] after peripheral nerve injury. The adaptive locomotor changes must rely on proprioceptive feedback and could be mediated by neural plasticity at both spinal [Frigon and Rossignol, 2008] and supraspinal levels [Lundborg, 2000].…”
Section: Discussionmentioning
confidence: 73%
“…Studies in animals have demonstrated that within days after peripheral nerve injury there are changes in electromyographic (EMG) activity of intact synergists and movement kinematics. For instance, denervation of selected ankle extensors in the cat -e.g., soleus (SO) and lateral gastrocnemius (LG) -led to an increase in activity of the remaining intact major ankle extensors [Pearson et al, 1999;Prilutsky et al, 2006;Frigon and Rossignol, 2008;Donelan et al, 2009;Maas et al, 2010]. This enhancement in muscle activity is accompanied by a marked increase in the ankle angle yield (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4-7 Since the late 1990s, several studies have shown that motor training after spinal cord transection can lead to improvement in performance (training-induced walking recovery 8 ), be very specific (eg, stand vs walk 9,10 ), and involve spinal circuits reorganization. 4,11,12 On the other hand, sustained exposure to nociceptive input is known to result in central sensitization, a phenomenon defined as an amplification of neural signaling within the CNS eliciting pain hypersensitivity , including increased synaptic efficacy in nociceptive neurons in the dorsal horn of the spinal cord. 13 Central sensitization is considered as a form of maladaptive plasticity as it is an important feature in many patients with chronic pain, and especially in “unexplained” chronic pain disorders.…”
Section: Introductionmentioning
confidence: 99%